2021
DOI: 10.3390/cells10071593
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mitochondrial Dynamics and Function on Retinal Ganglion Cell Susceptibility in Optic Nerve Disease

Abstract: The important roles of mitochondrial function and dysfunction in the process of neurodegeneration are widely acknowledged. Retinal ganglion cells (RGCs) appear to be a highly vulnerable neuronal cell type in the central nervous system with respect to mitochondrial dysfunction but the actual reasons for this are still incompletely understood. These cells have a unique circumstance where unmyelinated axons must bend nearly 90° to exit the eye and then cross a translaminar pressure gradient before becoming myelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 211 publications
(269 reference statements)
0
30
0
Order By: Relevance
“…Our current study builds on previous work that identified TMEM135 as a key protein involved in mitochondrial dynamics 3 , 7 , 20 , 21 , metabolic regulation 8 and oxidative stress in mice 3 . However, the molecular function of TMEM135 remains elusive.…”
Section: Discussionmentioning
confidence: 57%
“…Our current study builds on previous work that identified TMEM135 as a key protein involved in mitochondrial dynamics 3 , 7 , 20 , 21 , metabolic regulation 8 and oxidative stress in mice 3 . However, the molecular function of TMEM135 remains elusive.…”
Section: Discussionmentioning
confidence: 57%
“…As reviewed by others, perhaps the most accepted hypothesis involved in glaucoma pathogenesis currently may include the mechanical damage to the ONH induced by increased IOP, followed by vascular dysregulation (reduced ocular blood flow) and neuroinflammation (glial activation), which then disrupt axonal transport due to axonal mitochondrial function loss in the RGCs, ultimately leading to RGC axonal degeneration and RGC cell death (Figure 1) [58][59][60]. However, the combination of mechanisms described earlier may vary greatly among different glaucoma patients [60].…”
Section: Excitotoxicity Of Glutamatementioning
confidence: 99%
“…Neurons have a particularly polarized cell morphology that makes transport even more important, with several projections, including dendrites and a long axon, which extend far from the cell body, where most cell machinery is located [ 14 , 63 ]. In particular, the axons of RGCs span a considerable length running from the retina to the superior colliculus and the lateral geniculate nucleus at the posterior part of the brain [ 64 , 65 ]. Axonal transport is an ATP-dependent process, during which cytoskeleton-associated motor proteins actively carry different types of cargos along microtubules in the axons [ 15 ].…”
Section: Axonal Transport and Neurodegenerationmentioning
confidence: 99%
“…RGCs present some particular features which could make them even more prone to axonal transport disruptions. They are projection neurons with lengthy axons, estimated to reach 50–100 mm in primates, relying therefore on long-distance axonal transport [ 65 ]. Furthermore, the inner retina, where those cells are located, is known to have a high energy demand, and the ONH has normally an increased mitochondria density, a sign of more energy requirement.…”
Section: Axonal Transport and Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation